Kaniadakis-holographic dark energy: observational constraints and global dynamics. Issue 3 (29th January 2022) - Hernández-Almada, A; Leon, Genly; Magaña, Juan; García-Aspeitia, Miguel A; Motta, V; Saridakis, Emmanuel N; Yesmakhanova, Kuralay
ABSTRACT: We investigate Kaniadakis-holographic dark energy by confronting it with observations. We perform a Markov Chain Monte Carlo analysis using cosmic chronometers, supernovae type Ia, and Baryon Acoustic Oscillations data. Concerning the Kaniadakis parameter, we find that it is constrained around zero, namely around the value in which Kaniadakis entropy recovers standard Bekenstein-Hawking one. Additionally, for the present matter density parameter Ω _m^(0), we obtain a value slightly smaller compared to ΛCDM scenario. Furthermore, we reconstruct the evolution of the Hubble, deceleration, and jerk parameters extracting the deceleration-acceleration transition redshift as z_T = 0.86^+0.21_-0.14 . Finally, performing a detailed local and global dynamical system analysis, we find that the past attractor of the Universe is the matter-dominated solution, while the late-time stable solution is the dark-energy-dominated one.